Studi Penentuan Status Mutu Air Di Sungai Surabaya Untuk Keperluan Bahan Baku Air Minum - Citri Priyono, Thesa Septine; Yuliani, Emma; Sayekti, Rini Wahyu (Fakultas Teknik, Universitas Brawijaya, 2013)
The water of Surabaya River is the raw material of drinking water and one of water supply source for PDAM Surabaya. Over the last ten years pollution in Surabaya River is worsened. Pollution not only from domestic waste but also from existing industries around Surabaya River. This study aimed to determine the status of water quality in the Surabaya River. Determination water quality status in the Surabaya River conducted to closest monitoring station to the PDAM Waste Water Treatment Karangpilang. They are Cangkir Tambangan Monitoring Station, Bambe Tambangan Monitoring Stations, and Karangpilang Monitoring Station. The method used for the determination of water quality status are STORET and Pollution Index Method. Analysis of water quality status determination aims to determine the level of impurity in the nearest monitoring station. From the research it can be concluded, water quality status in Surabaya River is 49.44% heavily polluted by STORET for grade two. While 100% is being polluted by Pollution Index Method for grade two.Keywords: Water Quality Status, STORET, Pollution Index Method, Surabaya River